Linking Quality Perceptions to Student Decisions: A Study of Private Universities in Bandung, Indonesia - Efi Fitriani (Jurnal Ilmu Manajemen dan Ekonomika, 2026)
This study examines how students’ perceptions of quality at private universities in Bandung influence their college preferences and enrollment intentions to continue their master's studies. With the increasing number of private universities in Indonesia, particularly in Bandung, competition for students has grown. Perceived quality, including academic reputation, facilities, and service, plays a key role in students’ decision-making. Previous studies highlight the impact of institutional image, service quality, and promotional efforts on student enrollment intentions. However, there is limited research focusing specifically on how perceived quality influences college preference and enrollment intention in private universities in Bandung. This study fills this gap by examining the direct and indirect effects of perceived quality on student intention, mediated by college preference. The research questions address the influence of perceived quality on preferences, the impact of preferences on intention, and the mediating role of preferences between perceived quality and intention. Data were collected via questionnaires from 400 prospective and current students across 14 private universities in Bandung. Using Structural Equation Modeling with Partial Least Squares (SEM-PLS), the study tested relationships between perceived quality, college preference, and student intention. Findings reveal that perceived quality significantly influences college preference but has no direct significant effect on student intention. College preference significantly affects student intention and mediates the relationship between perceived quality and intention. The study suggests that universities should enhance perceived quality to shape student preferences and implement targeted strategies to convert them into actual enrollment decisions.